Untangling Centuries of South African Chinese Diasporas: Molluscs/Abalone, Ungulates/Rhinos and Equidae/Donkeys. Issue 2 (3rd April 2019) - Harris, Karen L.
Abstract: This article seeks to consider perceptions of the Chinese in the context of the illegal trade in molluscs (abalone), ungulates (rhino horn) and, more recently, equidae (donkey hides), which has scourged the coasts and hinterlands of South Africa for the Asian market for over half a century. Abalone is heralded as a delicacy for celebratory occasions, rhino horn is in high demand as a medicinal cure for a range of ailments and the more recent donkey hides are connected to the treatment of menopause and related conditions. Since its inception in the latter half of the twentieth century, this illegal trafficking by syndicates has been indelibly ascribed to the Chinese with hugely negative consequences and stereotyping becoming embedded in popular consciousness. This article attempts to untangle the perpetrators from the entangled Chinese diasporas by identifying three distinct historical waves of Chinese arrivals in South Africa and deliberates on how ignorance of this past has perpetuated a stereotyping which culminated in the current Chinese hate speech case in the Equality court.